Nanotechnology in Construction: Innovations, Applications, and Impacts (Journal of Civil Engineering Researchers, 2024)
Nanotechnology has emerged as a transformative force in the construction industry, revolutionizing traditional building materials and methods. This paper delves into the multifaceted applications of nanotechnology in construction, focusing on its impact on building coatings, materials, colors, insulation, and sensors. By incorporating nanoparticles like carbon nanotubes and titanium dioxide, construction materials gain enhanced mechanical properties and durability. Nano-coatings applied to surfaces such as glass, wood, and concrete offer benefits like water repellence, UV resistance, and antibacterial properties, contributing to energy efficiency and cost savings. Furthermore, advancements in self[1]healing concrete, fire-resistant glass, and smart surfaces demonstrate the potential of nanotechnology to address longstanding challenges in construction. The paper also explores the use of nanotechnology in paints, insulation, and sensors, highlighting innovations such as self-cleaning paints, antistatic coatings, and nano-acoustic insulators. Overall, the integration of nanotechnology into the construction sector promises improved product quality, energy efficiency, and longevity, heralding a new era of sustainable and resilient built environments.
Keywords: Nanotechnology; Nanomaterial in architecture Self-cleaning; Nano-Coating